2016
DOI: 10.1074/jbc.m115.668236
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Calmodulin Regulation of Different Isoforms of Kv7.4 K+ Channels

Abstract: Calmodulin (CaM), a Ca2؉ -sensing protein, is constitutively bound to IQ domains of the C termini of human Kv7 (hKv7, KCNQ) channels to mediate Ca 2؉ -dependent reduction of Kv7 currents. However, the mechanism remains unclear. We report that CaM binds to two isoforms of the hKv7.4 channel in a Ca 2؉ -independent manner but that only the long isoform (hKv7.4a) is regulated by Ca 2؉ /CaM. Ca 2؉ /CaM mediate reduction of the hKv7.4a channel by decreasing the channel open probability and altering activation kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 53 publications
3
17
0
Order By: Relevance
“…Often, facilitation is manifested by a left shift of the voltage-current relationship, such as that caused by apo-CaM for Kv7.2 and Kv7.4 channels [7,9,42], or holo-CaM for Kv7.1 [10]. However, changes in these parameters were not observed (Kv7.2/Kv7.3 heteromers) or were in the opposite direction (Kv7.2 homomers) [27].…”
Section: Discussionmentioning
confidence: 99%
“…Often, facilitation is manifested by a left shift of the voltage-current relationship, such as that caused by apo-CaM for Kv7.2 and Kv7.4 channels [7,9,42], or holo-CaM for Kv7.1 [10]. However, changes in these parameters were not observed (Kv7.2/Kv7.3 heteromers) or were in the opposite direction (Kv7.2 homomers) [27].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, calcium-bound CaM decreases Kv7.2 channel efficacy for PIP 2 , thereby inhibiting the M-current [44,90,91]. On the other hand, a recent study showed that splicing variants of Kv7.4 are differentially modulated by CaM [92]. This mechanism may explain why bradykinin induced suppression of the M-current is usually smaller than that by muscarinic agonists.…”
Section: Integrated Channel Suppressionmentioning
confidence: 99%
“…Protein Casein kinase 2 (CK2) and protein phosphatase 2A (PP2A) form a signaling complex with SK2 channels and regulate channel activity through phosphorylation/dephospohylation [63]. CK2 docks to an N-terminal binding site (125-RRALF-129 in SK2, equivalent to 15-RKRKL-20 in SK4) located at the base of S1.…”
Section: The Interaction Between Sk Channels and Calmodulin Is Regulamentioning
confidence: 99%
“…CK2 requires positively charged compounds to phosphorylate CaM [64], but these compounds are not present in functional excised patch experiments. As an alternative, it has been suggested that the charged residues at the base of S1 serve this purpose [63]. It has been shown that the mechanism involves phosphorylation of Thr 79 at the CaM lobe linker, leading to an increased dependency on PIP 2 binding, which is a lipid co-factor required for the function of SK2 channels [51].…”
Section: The Interaction Between Sk Channels and Calmodulin Is Regulamentioning
confidence: 99%